2003
DOI: 10.1152/ajpheart.00220.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional and pharmacological properties of canine ERG potassium channels

Abstract: We established HEK-293 cell lines that stably express functional canine ether-à-go-go-related gene (cERG) K(+) channels and examined their biophysical and pharmacological properties with whole cell patch clamp and (35)S-labeled MK-499 ([(35)S]MK-499) binding displacement. Functionally, cERG current had the hallmarks of cardiac delayed rectifier K(+) current (I(Kr)). Channel opening was time- and voltage dependent with threshold near -40 mV. The half-maximum activation voltage was -7.8 +/- 2.4 mV at 23 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 34 publications
(57 reference statements)
4
70
0
Order By: Relevance
“…Prolongation of QT is generally categorized into primary (inherited, familial, congenital, idiopathic) and secondary (disease, drug or toxin induced) (Moss 1999;Wang et al 2003;Gupta et al 2007). The pharmacological mechanism for QTi prolongation occurs as some drugs can cause effects that resemble the mutant gene hERG on chromosome 7 that encodes an abnormal K + channel protein, thus blocking cardiac voltage-gated potassium channels (IK r ) (Friedman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolongation of QT is generally categorized into primary (inherited, familial, congenital, idiopathic) and secondary (disease, drug or toxin induced) (Moss 1999;Wang et al 2003;Gupta et al 2007). The pharmacological mechanism for QTi prolongation occurs as some drugs can cause effects that resemble the mutant gene hERG on chromosome 7 that encodes an abnormal K + channel protein, thus blocking cardiac voltage-gated potassium channels (IK r ) (Friedman et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Certain drugs can directly delay the flow of electrolytes within cardiac tissue leading to QT prolongation. Such drugs share the potential to block the cardiac voltage-gated potassium channels, particularly the rapid component (IK r ) of the delayed rectifier potassium current (Fenichel et al 2006), which is biophysically and pharmacologically similar in human and dogs (Wang et al 2003). This effect has been described in antipsychotics, antibiotics, antiarrhythmics, gastrokinetics, anaesthetics and antihistamines, among others (Moss 1999;Dennis et al 2007;Gupta et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the outward delayed rectifier potassium channel (Kv11.1, human ether-a-go-go-related gene, hERG), potency was determined by measuring displacement of 35 S MK499 from HEK-293 cells stably expressing hERG. 21,22 As previously reported, 17 our initial follow-up to 1 focused on replacement of the two nitro groups with an eye toward improved selectivity over hERG compared to ROMK. Differentiation of the ROMK potassium ion channel activity from the hERG potassium ion channel activity was viewed as crucial due to the association between hERG channel blockade in vitro with QTc prolongation and risk of cardiac arrhythmias seen with a broad range of drugs.…”
mentioning
confidence: 94%
“…With these modifications, we have demonstrated that the combination of hydrophilic substitutions such as methylsulfone and lipophilic substitutions of CF 3 and OCF 3 on the benzamide phenyl ring resulted in significant …”
mentioning
confidence: 99%